Highly sensitive electrochemical sensor for the detection of Shiga toxin-producing E. coli (STEC) using interdigitated micro-electrodes selectively modified with a chitosan-gold nanocomposite. (10th September 2022) - Wasiewska, Luiza A.; Diaz, Fernando Garrido; Shao, Han; Burgess, Catherine M.; Duffy, Geraldine; O'Riordan, Alan
Highlights: A highly sensitive, label-free electrochemical sensor was developed for the detection of the stx1 gene from STEC using silicon chips comprising interdigitated microelectrodes (IDEs). A selective modification of sensor IDE with chitosan and probe DNA was confirmed using fluorescence. Applying an open circuit potential to the accumulator IDE allowed a more efficient accumulation of methylene blue between double-strand DNA. The specificity of the developed sensor was confirmed using DNA extracted from wild-type strains. Abstract: Shiga toxin-producing E. coli (STEC) is a food-borne pathogen of great concern due to the severity of the disease it can cause. A key pathogenicity factor is the ability to produce Shiga T Toxin 1 and 2, which are encoded by genes stx . Herein we report the development of a highly sensitive, label-free, electrochemical DNA-based sensor for the detection of the stx1 gene using interdigitated gold microelectrodes (IDEs) on fully integrated silicon chips. Each IDE comprised a working IDE, used for DNA probe immobilisation and an accumulator IDE. The working IDE was modified with gold nanoparticles (Au NPs) and chitosan gold nanocomposite to allow a covalent attachment of amine-modified probe DNA. The electrochemical detection was undertaken using methylene blue (MB) as a redox molecule, which intercalated into the double-strand DNA. The accumulator IDE was used for the electrostatic accumulation of the MB to the DNA binding region of the sensor thereby greatly enhancing sensitivity. The reduction of MB was recorded using square wave voltammetry (SWV). Using this approach, we achieved a linear response between 10 −16 and 10 −6  M of synthetic target strand with the lowest measured limit of detection of 100 aM after 20 min of hybridisation time. Subsequently, chromosomal DNA from four different E. coli strains (two stx1 positives and two stx1 negatives), Listeria monocytogenes and Bacillus cereus were used to confirm the selectivity of the presented method. This novel on-chip biosensor for the detection of STEC has the potential to be used for point-of-use detection.